THE EFFECT OF EXPERIMENTAL METHODS ON THE RESULTS OF NATURAL SCIENCE COGNITIVE LEARNING IN ELEMENTARY SCHOOL - ELYUMAIDA, RIKA; arlis, syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of the experimental method on cognitive learning outcomes of science in fifth grade students of SD Negeri 04 Simaung Agam. This type of research is experimental research with an experimental quasi design. The sample was selected using random sampling technique and purposive sampling. Two classes are taken to be an experimental class and a control class. From the results of the lottery, it was found that the VA class was the experimental class and the VB class was the control class. The results showed that the t-test score with a significant level of 0.005 was tcount (5.968)> ttable (2.0106). Thus it can be concluded that there is an effect of the use of experimental methods on cognitive learning outcomes of science of fifth grade students of SD Negeri 04 SimaungKata kunci : Experimen Method,Science Learning , Learning Outcomes